The Role of Regional Revenue Agency in Increasing Land and Building Tax Revenue (Pbb) Case Study nn Maulafa District, Kupang City - LONA, Aldha Solina; LINO, Maria Magdalena; ROZARI, Petrus de (Journal of Governance, Taxation and Auditing, 2024)
This research aims to determine the role of the Regional Revenue Agency of Kupang City in increasing land and building tax revenue in Maulafa District, Kupang City, and to identify factors that are obstacles to increasing PBB revenue. The type of approach used in this research is descriptive research using a qualitative approach. The research informants were nine people, and purposive sampling was used to take informants. In this research, there are four focuses to look at the role of the Regional Revenue Agency of Kupang City in increasing Land and Building Tax Revenue in Maulafa District, Kupang City, namely planning, determining targets for determining Land and Building Tax at the Regional Revenue Agency of Kupang City does not involve lower-level employees in this case officers in the field. First, distributing and billing are carried out in 9 sub-districts for three months starting from the issuance of the PBB SPPT. Second, the PBB and BPHTB sectors formed collection groups for several sub-districts to collect receivables and PBB for the current year. Third, the implementation of Land and Building Tax Services Role Model Week. Fourth, Bapenda collaborates with Law Enforcement Officials (APH), namely Satpol PP and the Prosecutor's Office. Several inhibiting factors that are often faced in efforts to increase Land and Building Tax revenues in Maulafa District, Kupang City, are Double-printing of PBB Tax Payable Letters, Unclear Taxpayer Addresses who are domiciled outside the region and data in Payable Tax Returns that are not up to date.